The Correlation Analysis of Maintenance Costs to Sei Siulak Deras Irrigation Network Infrastructure Performance - Dhana, Frans; Putranto, Dinar Dwi Anugerah; Susanti, Betty (Research Centre of Inorganic Materials and Complexs, 2019)
Sei Siulak Deras Irrigation Area is one of the Irrigation Areas located in Kerinci Regency based on the decision of Dinas Pekerjaan Umum dan Perumahan Rakyat (PUPR) regulations No.12/PRT/M/2015 concerning criteria and estabishment of Irrigation Area status with an area of 5,801 Ha. The authority for operational and maintenance implementation is handled by the Dinas PUPR of Jambi Province ( RTRW of Jambi Province, 2013). The performance of the Sei Siulak Deras irrigation network infrastructure is inseparable from the available maintenance budget, for this reason, it is necessary to conduct a study that analyzes the relationship between routine maintenance costs for the performance of irrigation network infrastructure in the Sei Siulak Deras irrrigation area of Kerinci District, Jambi Province. In this study an examination of the existing conditions of irrigation networks involving 1 observer and 6 irrigation workers, the irrigation network inspection using the standards issued by the Operation and Maintenance Agency of the Dinas PUPR of Jambi Province. From the results of the correlation analysis the cost of routine maintenance on the performance of irrigation network infrastructure is 0.9, this indicates a strong relationship between the two variables. While the maintenance budget allocated by the government to the maintenance of irrigation network infrastructure is very lacking, amounting to IDR 806,081,000 from the budget for the maintenance of irrigation network infrastructure of IDR 3,580,984,372.57.